Conservation of Resources, Psychological Distress, and Resilience During the COVID-19 Pandemic - Hadas Egozi Farkash; Mooli Lahad; Mooli Lahad; Stevan E. Hobfoll; Dima Leykin; Limor Aharonson-Daniel; Limor Aharonson-Daniel (Frontiers Media S.A., 2022)
Objectives: The Conservation of Resources (COR) theory suggests that stress results from threatened or actual loss of resources following significant life events. This study used COR theory as the framework to explore the reflection of loss of resources during the COVID-19 pandemic on psychological distress and resilience, in an adult Jewish Israeli population.Methods: We examined the association between background variables, stress, loneliness, concern, COVID-19-related post traumatic symptoms (PTS), resilience factors and COR via an online survey among 2,000 adults during April 2020.Results: Positive relationships were identified between resource loss and PTS (r = 0.66, p < 0.01), and between resource gain and resilience (r = 0.30, p < 0.01). Psychological variables were significantly associated with PTS and explained 62.7% of the variance, F (20, 1,413) = 118.58, p < 0.001.Conclusion: Loss of resources, stress, loneliness and concern were found to be risk factors for distress and PTS, whereas resilience factors played a protective role. We thus recommend using the COR theory to explore COVID-19 effects elsewhere.